Risk factors for postoperative delirium in patients undergoing orthopedic procedures: a systematic review and meta-analysis - Rio Suzuki; Aina Nakanishi; Masahiro Masuya; Keiko Fukuroku; Yukari Taneda; Yutaka Matsuura (PLoS ONE, 2025)
Delirium is a common complication in surgical patients following operative procedures; it often occurs in patients undergoing lower-extremity surgery. It is essential to identify and prevent the risk factors for postoperative delirium (POD) in these cases. We aimed to determine the risk factors for POD in patients who underwent lower-extremity surgery through a systematic review and meta-analysis. We included observational studies identifying risk factors for POD in patients undergoing orthopedic surgery. Data sources included the Cumulative Index to Nursing and Allied Health Literature and MEDLINE. We extracted the variables related to delirium that were analyzed by two or more studies meeting the eligibility criteria. A random-effects model was used to calculate the pooled odds ratio, standardized mean difference, and 95% confidence interval. Data were considered significant when p <  0.05. Twenty-seven studies with a total sample size of 9,044 were evaluated. Our meta-analysis revealed 20 risk factors for patients with POD undergoing orthopedic surgery, including age, cognitive scores, various preoperative laboratory values (such as serum albumin, C-reactive protein, and thyroid hormones), length of hospital stay, surgery and anesthesia duration, blood transfusion, and previous health conditions such as dementia and cardiovascular disease. Gathering preoperative and postoperative data was crucial for identifying high-risk patients for POD. In addition, preventive measures targeting POD risk factors could reduce its occurrence after orthopedic surgery.